2022
DOI: 10.1101/2022.06.01.494440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholecystokinin-expressing (CCK+) basket cells are key controllers of theta-gamma coupled rhythms in the hippocampus

Abstract: It has been shown that different inhibitory cell types underlie brain rhythmic and cross-frequency coupling output, but exactly how inhibitory cell types manifest their contributions to these outputs is far from clear. Brain rhythms and their couplings are functionally important in cognition and behaviour, and thus it is essential that we determine and understand these contributions. To do this, one needs simultaneous access to multiple cell types and population brain output in functionally relevant states. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…This model combines connections and cell types that were identified as critical for the existence of theta-gamma rhythms based on previous work using more detailed circuit models with nine different cell types (pyramidal cells, bistratified cells, PV-expressing basket cells, CCK-expressing basket cells, axo-axonic cells, Schaeffer collateral-associated cells, ivy cells, neurogliaform cells and oriens-lacunosum-moleculare cells) (Bezaire et al, 2016;Chatzikalymniou et al, 2021Chatzikalymniou et al, , 2022. Specifically, we have previously shown that the initiation of theta rhythms requires the presence of excitatory coupling between pyramidal cells (Chatzikalymniou et al, 2021), and that theta rhythms are lost with the removal of certain connections (Chatzikalymniou et al, 2022). In summary, we rationalize the use of a four cell-type microcircuit based on the more elaborate nine cell-type microcircuit (Bezaire et al, 2016;Chatzikalymniou et al, 2022) to examine theta-gamma coupled rhythms in CA1 hippocampus.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This model combines connections and cell types that were identified as critical for the existence of theta-gamma rhythms based on previous work using more detailed circuit models with nine different cell types (pyramidal cells, bistratified cells, PV-expressing basket cells, CCK-expressing basket cells, axo-axonic cells, Schaeffer collateral-associated cells, ivy cells, neurogliaform cells and oriens-lacunosum-moleculare cells) (Bezaire et al, 2016;Chatzikalymniou et al, 2021Chatzikalymniou et al, , 2022. Specifically, we have previously shown that the initiation of theta rhythms requires the presence of excitatory coupling between pyramidal cells (Chatzikalymniou et al, 2021), and that theta rhythms are lost with the removal of certain connections (Chatzikalymniou et al, 2022). In summary, we rationalize the use of a four cell-type microcircuit based on the more elaborate nine cell-type microcircuit (Bezaire et al, 2016;Chatzikalymniou et al, 2022) to examine theta-gamma coupled rhythms in CA1 hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we have previously shown that the initiation of theta rhythms requires the presence of excitatory coupling between pyramidal cells ( Chatzikalymniou et al, 2021 ), and that theta rhythms are lost with the removal of certain connections ( Chatzikalymniou et al, 2022 ). In summary, we rationalize the use of a four cell-type microcircuit based on the more elaborate nine cell-type microcircuit ( Bezaire et al, 2016; Chatzikalymniou et al, 2022 ) to examine theta-gamma coupled rhythms in CA1 hippocampus. The four cell types are pyramidal cells, bistratified cells and PV-expressing and CCK-expressing basket cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations